Medication nonadherence and its associated factors in psychiatric patients in India: A systematic review and meta-analysis - Parthasarathy Ramamurthy; Arya Jayasree; Susan Solomon; Vishnu V. Rudravaram; Vikas Menon; Pradeep Thilakan (Indian Journal of Psychiatry)
Medication nonadherence (MNA) poses a significant challenge in the management of major psychiatric disorders. The present study was undertaken to determine the prevalence of MNA among patients with psychiatric disorders in India and to identify the factors associated with MNA. The following databases were searched systematically: PubMed, Directory of Open Access Journals, and Google scholar. Articles originating from India published in peer reviewed English language journals before May 15, 2021 reporting the prevalence of MNA and associated factors among patients with psychiatric disorders were retrieved and the relevant data were abstracted. The pooled prevalence of MNA was calculated using the inverse variance method. Factors associated with MNA were synthesized and described. A total of 42 studies (pooled N = 6,268) were included in the systematic review. Among these, 32 studies (pooled N = 4,964) reported the prevalence of MNA and hence were eligible for meta analysis. The pooled prevalence of MNA was 0.44 (95% confidence interval [CI] 0.37-0.52). The pooled prevalence of MNA for psychotic disorders, bipolar disorders, and depressive disorders were 0.37 (95% CI, 0.28-0.46), 0.47 (95% CI, 0.23-0.72), and 0.70 (95% CI 0.60-0.78), respectively. Negative attitude toward medications, polypharmacy, greater severity of illness, lack of insight, and cost of medications were associated with MNA. Quality appraisal of the included studies revealed that most studies did not categorize and address nonresponders and did not provide any information on nonresponders. To conclude, about half of the patients with psychiatric disorders in India are nonadherent to their psychotropic medications. Evidence based interventions to improve medication adherence in these patients need to be developed and implemented proactively keeping in mind the factors associated with MNA.